(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Diabetes is an iceberg disease with many complications like cardiovascular disease &diabetic neuropathy. One of the most overlooked of all serious complications of diabetes is cardiovascular autonomic neuropathy (CAN), Autonomic nervous system dysfunction is one of the significant complications of diabetes mellitus and this is generally associated with a poor prognosis. Standard cardiovascular reflex tests are used to assess cardiovascular autonomic function. These include changes in heart rate during standing up and, Valsalva manoeuvre to assess cardiac parasympathetic activity. Aim: To analyse the role of heart rate during standing up and , Valsalva manoeuvre in diagnosing Cardiac Autonomic Neuropathy. Method: In this cross sectional study, 30 diabetics were compared with 30 non-diabetics (plasma glucose level between 80-120 mg %) for their autonomic functions. Each subject was evaluated for cardiovascular autonomic neuropathy by heart rate during standing up and , Valsalva manoeuvre Statistically analysis was performed using t test. Results: There was statistically significant (p<0.05 )association of change in heart rate on standing change in Valsalva Response to diabetic autonomic neuropathy Conclusion: Diabetes mellitus is one of the systemic disease which leads to autonomic dysfunctions when compared to non diabetes which may be because of increased duration of disease.